(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The tradition of reviewing newly published scientific, literary books and scientific articles, new works of art by specialists has developed earlier in countries with a developed written literary language and science. Writing reviews in the Kazakh language began at the beginning of the 20th century, when various books in the national language began to appear. The person, who systematically engaged in this work and wrote the first reviews of textbooks, scientific and literary books in the Kazakh language was one of the Kazakh intellectuals - Alikhan Bokeykhan. He paid special attention to the issue of publishing books in the national language, their quality and translation, continuously wrote reviews of various published literature, laid the foundations for the formation of the Kazakh reviewing genre, set an example and showed the way in this field. The article comprehensively analyzes the goals of A. Bokeykhan when writing reviews, the specifics of his reviews, and also discusses the role of such brief analytical works at the beginning of the 20th century. The types and language differences of the reviews written by him are shown. Modern types of reviews, their stylistic and structural features and their own character as a separate genre are determined. Scientific review has become the only way to analyze and evaluate scientific work, and literary review has become an integral part of literature. The article specifically mentions the works of the intellectual of Alash, who wrote the first review of Kazakh books, the period of the beginning of this genre and the ways of its formation for the first time . Determining his contribution to book criticism, reviewing the first Kazakh books, the formation of this genre in the study of the heritage of a multifaceted personality, the owner of encyclopedic knowledge, is an important task of Alikhan studies